Proceso de atención de enfermería en paciente masculino de 77 años de edad con edema pulmonar cardiogénico asociado a insuficiencia cardiaca. - Martínez Sellan, Juan Carlos (2019)
The present clinical case was elaborated with the objective of applying the Nursing Care Process in a 77-year-old male patient who comes to the General Hospital Liborio Panchana Sotomayor Emergency Area due to severe respiratory distress, saturating 85% in ambient air, fatigue, general malaise, does not tolerate decubitus, has generalized crepitant rales, lower limb edema plus preserved diuresis, with respiratory frequency of 35 per minute with use of accessory muscles, blood pressure of 210/80 mmhg, heart rate of 125 beats per minute, has a history of controlled arterial hypertension, gouty arthritis, controlled diabetes mellitus and grade 2 chronic renal failure. Resident doctor decides to enter the Intensive Care Unit with definitive diagnosis of Cardiogenic Pulmonary Edema associated with heart failure. Staying in Intensive Care for 10 days, the vital signs were monitored every hour, control intake and excreta through water balance, monitoring and care of the invasive mechanical ventilation, supine decubitus position, daily weight, central venous catheter management more Nursing care, welfare and patient comfort. Through the collection of these data and the cephalocaudal assessment of the patient, we will be able to apply the development of the nursing care process in the approach to cardiogenic pulmonary edema associated with heart failure.